Cookies are required for login! Check our privacy consent banner for more details.
Help Me please.
Solve for x
3√x - m=n
This is pretty straightforward.......we want x on one side of the equation by itself
cubrt(x) -m = n add m to both sides of the equation
cubrt(x) = n+m Now cube each side
x = (n+m)^3
Solve for x:
x^(1/3) - m = n
Isolate terms with x to the left hand side.
Add m to both sides:
x^(1/3) = m + n
Eliminate the cube root on the left hand side.
Raise both sides to the power of three:
x = (m + n)^3 = m^3 + 3m^2n + 3mn^2 + n^3